Comparison on carbon coating over silica spheres with different carbon sources. (June 2015) - Lu, B. H.; Zhou, J.; Li, Y. Y.; Xiao, W.; Wang, H. L.
<x content-type="archive" xml:space="preserve">Abstract</x> Three wet chemical routes, namely, glucose assisted hydrothermal, sucrose assisted evaporation and hexadecyl trimethyl ammonium bromide assisted processes, for carbon coating on silica nanospheres were investigated and compared. The effects of the synthetic parameters on the composition and microstructure of the final products were discussed and rationalised. The present discussion highlighted the importance of tuning the interaction between carbon source and surface of silica spheres on the microstructure and content of carbon coating.